FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN HIPERTENSI PADA KEHAMILAN DI KLINIK PRATAMA ZR ROMAULI TAHUN 2020 - R. Oktaviance. S; Aprilita Br Sitepu (STIKes Santa Elisabeth Medan, 2020)
Introduction: The pregnancy period begins with the union of spermatozoa and ova and continues with nidation or implantation. If calculated from the time of fertilization until the birth of a baby, a normal pregnancy will take place within 40 weeks or 9 months according to international calendar. Hypertension in pregnancy is hypertension that occurs when pregnancy lasts at the womb minggu20 weeks of age. There are many risk factors for hypertension in pregnancy, which can be grouped, namely primigravida, primipaternity, hyperplacentosis, age 35 years, family history of having preeclampsia / eclampsia, large placental period (gameli, trophoblastic disease), obesity and kidney diseases and hypertension with hypertension. had existed before pregnancy (Sarwono, 2018). Method: The purpose of this study was to determine the description of factors of knowledge, age and physical activity in pregnant women about hypertension in pregnancy in ZR Romauli clinic. This type of research is descriptive conducted in the village of bawodobara. The population of all pregnant women check up in ZR Romauli clinic, a sample of 45 respondents. The sampling technique is total sampling. Data collection uses primary data with a questionnaire. Data analysis using univariate analysis for frequency distribution.. Result: The results of the study of the level of knowledge about pregnancy hypertension showed that the majority of respondents in Bawodobara village had sufficient knowledge (50%), when viewed from the age factor, it showed that most pregnant women in Bawodobara village were in productive age, 20 - 35 years old (75%) and from the activity factor Physical analysis performed by pregnant women is that ZR Romauli clinic shows that most of them have strenuous activities (40%). Discussion: From this study, the researchers concluded that health workers must increase the knowledge and insight of pregnant women who are hypertensive in pregnancy and those who are not hypertensive in pregnancy, namely by conducting counseling / extension signs of hypertension in pregnancy.